Biomarkers for systemic sclerosis - tools for diagnosis and treatment - Yehudina, Ye; Golovach, I (Annals of Mechnikov’s Institute, 2019)
Introduction. Systemic sclerosis (SSc) is an autoimmune disease characterized by skin and internal organ fibrosis with prior vascular and immune dysfunction. Depending on the cutaneous fibrosis degree, SSc is divided into two main subtypes: limited skin SSc (LT-SSc) and diffuse skin SSc (DF-SSc). This classification is characterized by association with certain autoantibodies that specifically define these clinical phenotypes. Despite ongoing research, so far only a few biomarkers of SSc have been fully validated, approved and implemented into practice. Material and methods. This paper presents a literature review of promising SSc prognostic biomarkers, biomarkers of disease activity, skin fibrosis and internal organ lesion with the aim of providing comprehensive information on the applicability of biomarkers for research and clinical use. A literature search was conducted in the PubMed, MedLine, Scopus and Embase databases from 2000–2018. Keywords used for search: systemic sclerosis, anti-nuclear autoantibodies, non-specific autoantibodies, biomarkers. Results and discussion. The presence of autoantibodies is the central determining aspect of autoimmune diseases. Autoantibodies are found in the initial diagnosis of more than 95% of SSc patients and associated with different disease subtypes and the clinical course severity. Antitopoisomerase I (ATA), or anti-Scl-70 antibodies, and anticentromere (ACA) antibodies are the most widely used SSC diagnostic biomarkers. ATA is observed mainly in patients with DF-SSc, associated with a worse prognosis, increased mortality, the digital ulcer development, pulmonary fibrosis and heart damage. ACA is detected in 90% of patients with LT-SSc. In patients with Raynaud’s phenomenon, ACA predicts the occurrence of LT-SSc. ACA positivity correlates with a more favorable prognosis and lower mortality compared with positivity for other autoantibodies associated with SSc. Antibodies against RNA polymerase III (anti-RNP III) are highly specific for patients with SSc (98–100%). Anti-RNP III is associated with DF-SSc, debut in old age, a renal crisis and a high risk of a malignant tumor developing. Anti-Th/To are clinically associated with LT-SSc and are the marker for the worst survival. Anti-U3RNP is often associated with DF-SSc, the visceral organ involvement, especially kidneys and heart. The presence of UI RNP antibodies is associated not only with SSc, but also with systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), myositis, many patients have criteria for mixed connective tissue disease. More recently, autoantibodies to type 1 angiotensin II receptor (AT1R) and type A endothelin-1 receptor (ETAR) have been found to be elevated in the serum of most patients with SSc and are associated with vascular and fibrous complications. Relatively rare and less specific antibodies are anti-U11/U12 RNP, PM/Scl antibodies, antibodies against estrogen receptors α, anti-endothelial cell antibodies, anti-fibroblast antibodies, anti-platelet-derived growth factor receptor antibodies. It has been shown that the elevated expression of pro-fibrotic miRNAs and reduced expression of antifibrotic miRNAs are important factors in the developments of fibrosis in SSc. Unlike other autoimmune diseases, such as SLE or RA, for many patients with SSc it is difficult to assess the presence of current inflammation, it is not easy to determine the blood vessel and tissue fibrosis, especially at an early stage of the disease. Biochemical markers candidates for assessing the activity and severity of the disease in SSc were obtained based on the presence of an association with target organ damage. Serum von Willebrand factor, glycoprotein Krebs von den Lungen 6, procollagen-III aminoterminal-propeptide, tissue inhibitor of matrix metalloproteinase-1, IL-6, growth factor differentiation 15, the serum level of cartilage oligomeric matrix protein, angiopoietin/Tie2 and hyaluronic acid showed a significant correlation with both the activity and the severity of the disease. Conclusion. Thus, serum autoantibodies are considered important biomarkers for early and accurate diagnosis of SSc and are associated with distinctive clinical subgroups and various prognostic signs of this disease. It has been demonstrated that some autoantibodies directed against autoantigen specific targets induce inflammation, activate fibroblasts, promote the synthesis and deposition of collagen, and activate endothelial cells, participating in the pathogenesis of SSc. Understanding the pathogenic role of autoantibodies in SSc can help identify new therapeutic targets for this complex disease.